Phase I study utilizing a novel antigen-presenting cell-targeted vaccine with Toll-like receptor stimulation to induce immunity to self antigens in cancer patients - Morse, Michael A. (2011)
PURPOSE: The use of tumor-derived proteins as cancer vaccines is complicated by tolerance to these self antigens. Tolerance may be broken by immunization with activated, autologous, ex vivo generated and antigen-loaded, antigen-presenting cells (APC); however, targeting tumor antigen directly to APC in vivo would be a less complicated strategy. We wished to test whether targeted delivery of an otherwise poorly immunogenic, soluble antigen to APC through their mannose receptors (MR) would induce clinically relevant immunity. EXPERIMENTAL DESIGN: Two phase I studies were performed with CDX-1307, a vaccine composed of human chorionic gonadotropin beta chain (hCG-β) fused to a MR-specific monoclonal antibody, administered either locally (intradermally) or systemically (intravenously) in patients with advanced epithelial malignancies. An initial dose-escalation of single agent CDX-1307 was followed by additional cohorts of CDX-1307 combined with GM-CSF and the Toll-like receptor (TLR)-3 agonist poly-ICLC and TLR7/8 agonist resiquimod to activate the APC. RESULTS: CDX-1307 induced consistent humoral and T cell responses to hCG-β when co-administered with TLR agonists. Greater immune responses and clinical benefit, including the longest duration of stable disease, were observed with immunization combined with local TLR agonists. Immune responses were induced equally efficiently in patients with elevated and non-elevated levels of serum hCG-β. Antibodies within the serum of vaccinated participants had tumor suppressive function in vitro. Toxicity consisted chiefly of mild injection site reactions. CONCLUSIONS: APC targeting and activation induce adaptive immunity against poorly immunogenic self antigens which has implications for enhancing the efficacy of cancer immunotherapy.